Os benefícios da implantação da hidrovia Araguaia Tocantins para o transporte de mercadorias - Oliveira, Ana Caroline Dorxas de (Universidade Federal do Tocantins, 2020)
This paper discusses the implementation of the Araguaia/Tocantins waterways and improving the existing infrastructure, the main objectives: to identify the potential of the waterway, to analyze your apparatus for transporting loads, to identify its socio-economic impacts and analyze the potential of the infrastructure existing. The nature of the research, this paper resorted to literature and documentary research. As the results could be concluded that the implementation of the waterway becomes feasible when we analyze all the advantages that it will bring to society as a whole, it is a competitive advantage for existing industries in the region. Moreover, it will attract the installation of large industries, creating jobs and economic development to the region. As to the existing infrastructure, the same is of great importance to waterway, because it able for interconnect the modal, and the improvement in its infrastructure will maximize the potential of the waterway and its region.